Pengaruh Literasi Keuangan, Inklusi Keuangan Dan Minat Menggunakan E-Commerce Terhadap Kinerja Umkm Di Kecamatan Kuranji - Wahyu Awalul Ramadhan; Indrayeni (CV. ITTC INDONESIA, 2024)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia are one of the priorities in national economic development and have an important role in the country's economy. The large contribution of MSMEs to economic development in Indonesia requires MSME players to keep trying and always be ready to compete with other MSMEs. This research aims to determine the influence of Financial Literacy, Financial Inclusion, Interest in Using E-Commerce on MSME Performance. The population in this research is MSMEs in Kuranji sub-district. The sampling method used in this research is the purposive sampling method, so that 150 MSMEs in Kuranji sub-district are obtained. This research data was obtained from the results of a questionnaire. The data analysis techniques used are descriptive statistical analysis, data quality testing, regression analysis and hypothesis testing. The results of this research show that Financial Literacy has a positive and significant effect on the financial performance of MSMEs, Financial Inclusion has a positive and significant effect on the performance of MSMEs and Interest in Using E-commerce on the performance of MSMEs has a significant positive effect on the performance of MSMEs.